2022
DOI: 10.3389/fphar.2021.760507
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Nerve Growth Factor (Cenegermin)–Driven Corneal Wound Healing Process: An Evidence-Based Analysis

Abstract: Purpose: To evaluate anterior segment optical coherence tomography (AS-OCT) to detect the wound healing process as per monitoring the effectiveness of cenegermin to treat moderate to severe neurotrophic keratoplasty.Methods: A retrospective chart review was realized to identify patients treated with cenegermin at the Clinica Oculistica, University of Genoa, Italy. All patients underwent careful examinations at baseline and follow-up visits. AS-OCT scans centered on the minimum corneal thickness (CT) area were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(45 reference statements)
1
5
0
Order By: Relevance
“… 12 Chronic inflammation seen in DED can lead to damage in corneal sensory nerves ultimately leading to progression to NK. 7 , 8 , 9 The frequencies for the etiologies of NK in the recent studies cited 7 , 8 , 9 , 10 are generally in line with what was observed in the pivotal trials of neurotrophic growth factors to treat Stage 2 and 3 NK. There were 17/156 eyes (10.9%) in the REPARO clinical trial 13 and 6/48 eyes (12.5%) in the US clinical trial 14 that had dry eye disease listed as the underlying cause of NK.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“… 12 Chronic inflammation seen in DED can lead to damage in corneal sensory nerves ultimately leading to progression to NK. 7 , 8 , 9 The frequencies for the etiologies of NK in the recent studies cited 7 , 8 , 9 , 10 are generally in line with what was observed in the pivotal trials of neurotrophic growth factors to treat Stage 2 and 3 NK. There were 17/156 eyes (10.9%) in the REPARO clinical trial 13 and 6/48 eyes (12.5%) in the US clinical trial 14 that had dry eye disease listed as the underlying cause of NK.…”
Section: Introductionsupporting
confidence: 80%
“…6 More recently, it has been determined that chronic dry eye disease (DED) disease can also cause corneal nerve damage since eye lubrication and nourishment is reduced leading to corneal nerve damage. 7 , 8 , 9 In fact, any condition that can cause corneal damage may lead to NK symptoms including DED, exposure keratitis, limbal stem cell deficiency, surgical damage to the cornea, and Sjögren's syndrome. 4 , 7 , 8 , 9 , 10 A recently published retrospective study cites dry eye as the underlying cause of NK in 8/63 eyes (12.7%), including 2/63 eyes (3.2%) that were attributed to Sjögren's syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a neurotrophic factor and immunomodulatory factor, nerve growth factor (NGF) plays an important role in the survival, growth, and differentiation of sensory neurons, as well as in promoting wound healing [4] . Recombinant human NGF (rhNGF) has the same structure as endogenous NGF, so it can quickly promote corneal wound healing and improve the corneal perception and tear production [5] . RhNGF (cenegermin, 20 µg/mL of rhNGF) has been clinically used in Europe, United States, etc, and has been shown to aid in the recovery of corneal nerve function [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%